Antibacterial domestic ceramics - Fang Kun (2016)
The invention discloses antibacterial domestic ceramics. The domestic ceramics are made from the following raw materials, by weight part,2-3 of sodium pyrophosphate, 20-24 of pottery clay, 16-19 of six-ring rock, 2-3 of cobalt oxide, 10-14 of silver nitrate, 2-3 of boron carbide, 4-6 of nanometer titanium oxide, 11-14 of vermiculite, 40-45 of coal ash, 35-40 of white glaze spheres, 6-8 of waste glass, 10-14 of maifan stone, 21-25 of green tea, 14-17 of orange peels, 6-8 of shell powder, 4-6 of shrimp shell powder, 0.2-0.3 of polyvinyl alcohol, 0.2-0.3 of tributyl phosphate, and a proper amount of deionized water. The domestic ceramics are healthy and eco-friendly, can slowly release microelements, and are excellent in antibacterial property. The domestic ceramics can last for a long time and protect people's life and health. 本发明公开了种抗菌日用陶瓷，由以下重量份的原料制备制成：焦磷酸钠2-3、陶土20-24、六环石16-19、氧化钴2-3、硝酸银10-14、碳化硼2-3、纳米氧化钛4-6、蛭石11-14、粉煤灰40-45、白釉球35-40、废玻璃6-8、麦饭石10-14、绿茶21-25、橙子皮14-17、贝壳粉6-8、虾壳粉4-6、聚乙烯醇0.2-0.3、磷酸三丁酯0.2-0.3、去离子水